In vitro studies of curcuma caesia Roxb. for bioactive compounds production and screening for antibacterial properties - Fong, Yin Mei (2015)
Curcuma caesia is a medicinal plant which originated from India. This species is consisted of flavanoids, alkaloids, amino acid, protein, curcuminoids, volatile oils and phenolics. The study of this curcuma was divided into three main parts which were plant tissue culture, extraction and antibacterial testing. In plant tissue culture aspect, shoot induction, callus induction and cell suspension culture were studied. In shoot induction experiment, different concentrations of hormones such as BAP, BAP in combination with IBA, BAP in combination with NAA, KIN and TDZ were studied. The best treatment for shoot induction experiment was reported in MS medium supplemented with 8.0 mg/L BAP with mean of 4.00±0.82 shoots. However, for economic feasibility purposes, 1.0 mg/L with similar result was chosen as the best concentration for shoot induction. Then, the in vitro plant produced from these experiments were dried and used for extraction and antibacterial test. For callus induction experiment, different hormones were used alone or in combination had been tested. The experiments were carried out using 2, 4-D and BAP alone or in combination, 2, 4-D in combination with KIN, NAA alone or together with BAP. From the study, the combination of 2.0 mg/L BAP with 0.5 mg/L 2, 4-D was the best treatment to induce callus from leaf and root explants with percentage of 94.64 % and 100.00 % respectively. Callus induced in this experiment was extracted using methanol for chemical compounds analysis. In the cell suspension culture, different volumes of medium, plant growth regulators, growth pattern and application of casein hydrolysate had been studied. Chemical compositions for cell suspension induced from different concentrations of casein hydrolysate were determined. The best medium volume for both leaf and root cell growth was in 40 mL liquid MS medium supplemented with 2.0 mg/L BAP and 0.5 mg/L 2, 4-D. As compared to medium supplemented with casein hydrolysate, both leaf and root cell had recorded high cell growth in medium without casein hydrolysate. Both cell from the control medium and medium supplemented with casein hydrolysate treatment had recorded total of 24 different compounds presence in the leaf cell and 49 different compounds from roots cell. From the results, roots cell grown in no casein hydrolysate liquid medium had showed the highest number of natural compounds. The highest yield of methanolic extracts was recorded by in vitro leaves (9.07%) followed by mother plant leaves (6.18 %) and mother plant roots (6.14%). The results showed that there were 60 compounds from mother plant leaves, 54 compounds from mother plant roots, 55 compounds from in vitro leaves, 22 compounds from in vitro roots, 20 compounds from leaf callus extract and 12 compounds from root callus extract. Most of the plant extracts were from hydrocarbon alkane, saturated and unsaturated fatty acid, aliphatic hydrocarbon, glycol ether, carboxylic acid, steroid, glycosides, fatty alcohol, derivatives benzene, and ester group. All the plant extracts had recorded promising results to inhibit all the bacteria tested such as L. monocytogenes, B. subtilis, S. typi, and E. coli in Kirby Bauer disc diffusion method. For MIC using ICD method, in vitro roots had recorded the lowest concentration (3.125 mg/ml) to be used to inhibit all both gram positive and gram negative bacteria.